An Assessment Tool for Public Procurement Agencies in Health Sector in India - World Bank (Washington, DC, 2013)
The Government of India (GoI) under its common minimum program is enhancing central funding to states for effective delivery of essential health services to underserved populations residing in the rural areas of the country. Flexible financing is being provided to states under the National Rural Health Mission (NRHM) to develop locally relevant strategies to improve service delivery and implement evidence-based interventions to enhance health outcomes of centrally sponsored schemes in the health sector. Such rapid scaling-up of central allocations for different health sector schemes will involve massive procurement of health sector goods by the states and districts that have capacity constraints to undertake health sector procurement The NRHM framework notes that continued central procurement is not a solution and proposes a phased decentralization of procurement to states and districts. This note supports the approach of phased decentralization through development of an assessment tool for systematically identifying the procurement capacity constraints at state level.